Tradition of the Profit Sharing System for Cultivating Rice Fields According to a Sharia Economic Perspective - A.Dinda Try Andini; Zulkifli; Hartas Hasbi (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2024)
This research aims to analyze the tradition of profit-sharing systems in rice cultivation in Biru Village, Tanete Riattang District, Bone Regency, from an Islamic economic perspective. The profit-sharing tradition has long been an integral part of agricultural practice in this area, where farmers and landowners collaborate to maximize production. The study uses a qualitative approach with a case study method, involving field observations and in-depth interviews. Key informants include cultivating farmers and landowners The findings indicate that the profit-sharing system in Biru Village generally adheres to basic Islamic economic principles such as justice (al-adl), mutual agreement (al-muwafaqah), and transparency (al-shafafiyah). Practically, the division of results between farmers and landowners is agreed upon based on mutual consent and each party's contribution to production. However, challenges such as the need for better documentation and transaction reporting exist. The study concludes that while the profit-sharing system in Biru Village aligns with Islamic economic principles, there is room for improvement, particularly in education and technical implementation. Recommendations include enhancing training programs and socialization on Islamic economics for farmers and landowners, as well as developing more transparent and accountable documentation mechanisms. It is hoped that this profit-sharing tradition can continue to develop and provide greater benefits to the local community’s welfare.